Analisis Kesesuaian Lahan Untuk Permukiman Wilayah Pesisir Kabupaten Boalemo - Hardin, Hardin; Yusuf, Daud; Lahay, Rahmat Jaya (Universitas Negeri Gorontalo, 2025)
Structuring and analyzing land suitability is very important for planning coastal area development because land use in coastal areas often gives rise to community conflicts and overlapping tumpeng. The aim of this research is to provide land for settlements on the coast of Boalemo Regency. Physical aspects of land, accessibility and availability of environmental infrastructure are the variables of this research. Geographic information system software is used to conduct spatial research. The area that is very suitable for settlement is 1667.02 (1.74%). Sufficiently suitable area for the organization is 58850.71 (61.51%). The marginal suitable area for the organization is 32944.80 (34.44%). Areas that are not suitable for the organization are 2088.04 (2.18%) and areas that are not permanently suitable for the organization are 121.08 (0.13%).